Mitochondrial targeted astaxanthin liposomes for myocardial ischemia-reperfusion injury based on oxidative stress. (August 2022) - Gao, Feng; Zhao, Yongcheng; Zhang, Bin; Xiao, Chunwei; Sun, Zhanfa; Gao, Yuan; Dou, Xueyong
Myocardial ischemia-reperfusion injury (MI/RI) refers to the clinical state of decreased coronary blood flow caused by various causes. The main pathogenesis of MI/RI is mitochondrial oxidative damage. In this study, we designed a novel mitochondrial targeted astaxanthin (AST) liposome, namely, STPP-AST-LIP, targeting mitochondria of H9c2 myocardial cells. STPP-AST-LIP not only reduced the production of mitochondrial reactive oxygen species (ROS), but also increased the survival rate of MI/RI H9c2 cells. In addition, rat experiments further confirmed that STPP-AST-LIP could improve myocardial cardiac function in MI/RI rats, significantly inhibited apoptosis of myocardial cells, and had a protective effect on the heart of rats after MI/RI.